Parallelizable microfluidic dropmakers with multilayer geometry for the generation of double emulsions. Issue 1 (29th November 2019) - Nawar, Saraf; Stolaroff, Joshuah K.; Ye, Congwang; Wu, Huayin; Nguyen, Du Thai; Xin, Feng; Weitz, David A.
Abstract : We present a multilayer dropmaker geometry that enables the modular fabrication of microfluidic devices containing precisely patterned channel surface wettability. The platform is used for the scalable production of uniform double emulsion drops. Abstract : Microfluidic devices enable the production of uniform double emulsions with control over droplet size and shell thickness. However, the limited production rate of microfluidic devices precludes the use of monodisperse double emulsions for industrial-scale applications, which require large quantities of droplets. To increase throughput, devices can be parallelized to contain many dropmakers operating simultaneously in one chip, but this is challenging to do for double emulsion dropmakers. Production of double emulsions requires dropmakers to have both hydrophobic and hydrophilic channels, requiring spatially precise patterning of channel surface wettability. Precise wettability patterning is difficult for devices containing multiple dropmakers, posing a significant challenge for parallelization. In this paper, we present a multilayer dropmaker geometry that greatly simplifies the process of producing microfluidic devices with excellent spatial control over channel wettability. Wettability patterning is achieved through the independent functionalization of channels in each layer prior to device assembly, rendering the dropmaker with a precise step between hydrophobic and hydrophilic channels. This device geometry enables uniform wettability patterning of parallelized dropmakers, providing a scalable approach for the production of double emulsions.